ADAPTASI GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA BELAJAR DI MADRASAH TSANAWIYYAH AL-KAUTSAR DENDANG KABUPATEN TANJUNG JABUNG TIMUR - Gumelar; Maisah; Edy Kusnadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teachers’ adaptation in implementing the Merdeka Curriculum at Madrasah Tsanawiyyah Al-Kautsar Dendang, Tanjung Jabung Timur Regency. The focus of this research includes teachers’ adaptation in lesson planning, learning implementation, and assessment systems in accordance with the principles of the Merdeka Curriculum. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The research informants consisted of the head of the madrasah, teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation.The results show that teachers’ adaptation in implementing the Merdeka Curriculum has undergone significant changes. In lesson planning, teachers have shifted from using traditional lesson plans to more flexible teaching modules and have begun implementing diagnostic assessments to identify students’ initial abilities. In the implementation stage, there has been a shift from teacher-centered learning to student-centered learning by applying group discussions, Project-Based Learning, and Problem-Based Learning. In terms of assessment, teachers have implemented more comprehensive evaluations by assessing learning processes, attitudes, and skills, as well as providing descriptive feedback on students’ development. However, several challenges were identified, including limited understanding of the Merdeka Curriculum concepts, inadequate facilities and infrastructure, and the need for improved classroom management in active learning settings. Overall, the implementation of the Merdeka Curriculum at Madrasah Tsanawiyyah Al-Kautsar Dendang shows a positive direction toward more flexible, contextual, and student-centered learning. Keywords: Teacher Adaptation, Merdeka Curriculum, Curriculum Implementation, Islamic Junior High School.